IMPLIKASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PEDESAAN TERHADAP KETERSEDIAAN INFRASTRUKTUR DI KECAMATAN SORKAM KABUPATEN TAPANULI TENGAH - Sri Ayu Ningsi; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to analyze the implication PNPM rural to the availability of infrastructure. The study was conducted in 4 village namely Sorkam, Naipospos Barat, Teluk Roban, and Bottot with the quantity of samples is 91 hauseholds. The analysis method that used in this study is descriptive analysis, simple regression analysis, paired sample t test and the measurement scale is likert scale. The descriptive analysis result showed that the implementation of PNPM rural in sorkam is dominantly used for the development and the improvement of basic infrastructure. The simple regression estimation’s result showed that impact PNPM rural to the availability of the infrastructure in sorkam is significantly positive. While the paired sample t test showed that the availability of infrastructure has a positive effect on level of people’s income in sorkam.Keyword: PNPM-MPd, Availability of the Infrastructure, Income level, Descriptive Analysis, Simple Regression, and Paired Sample t Test.